Predicting discharge from long-term forensic treatment: patients characteristics, protective factors, needs and treatment-related factors study in the Czechia. Issue 1 (2nd January 2022) - Páv, Marek; Sebalo, Ivan; Vňuková, Martina; Pabiánová, Štěpánka; Málová, Veronika; Hollý, Martin; Perkins, Derek
ABSTRACT: One of the challenges in forensic psychiatry is determining when an inpatient is ready to be discharged and return to the community. The comprehension of factors that predict extended treatment or discharge is relatively limited. We assessed the treatment progress of a cohort of forensic inpatients (N=80) divided into two groups: discharged patients and patients who remain detained. We derived socio-demographic and clinical variables from each patient's medical records and scores on the HoNOS-Secure, GAF, and SAPROF scales. The dataset was subjected to logistic regression and Chi-square analysis to determine the relevant factors. We gained insights into illness as a strong predictor of discharge, which is also associated with the patient's general compliance with the facility program and participation in occupational therapy. The majority of our sample has moderate or severe functional impairment according to GAF. The instruments used can capture dynamic factors related to discharge or continuing hospitalization, namely the SAPROF total or external factors score, the HoNOS-Secure subscale, and significant items from the HCR-20 clinical and risk subscales.